2021
DOI: 10.1155/2021/9487319
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Therapy Rehabilitation in Stroke: A Scoping Review of Upper Limb Recovery and Brain Activities

Abstract: Background. Mirror therapy (MT) has been used as a treatment for various neurological disorders. Recent application of electroencephalogram (EEG) to the MT study allows researchers to gain insight into the changes in brain activity during the therapy. Objective. This scoping review is aimed at mapping existing evidence and identifying knowledge gaps about the effects of MT on upper limb recovery and its application for individuals with chronic stroke. Methods and Materials. A scoping review through a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
5
0
2
Order By: Relevance
“…Finally, the study of these neurophysiological measures could provide useful information on the brain mechanisms that mediate the effects of various therapies used in the rehabilitation field. Therefore, by exploring the neurophysiological mechanisms that are most activated by specific rehabilitation treatments, it will be possible to select the most appropriate behavioral rehabilitation treatment for the patient, based on the alterations revealed by the EEG, such as mirror therapy, functional electrical stimulation and robotics (Jia et al 2022 ; Jaafar et al 2021 ; Daly and Ruff 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the study of these neurophysiological measures could provide useful information on the brain mechanisms that mediate the effects of various therapies used in the rehabilitation field. Therefore, by exploring the neurophysiological mechanisms that are most activated by specific rehabilitation treatments, it will be possible to select the most appropriate behavioral rehabilitation treatment for the patient, based on the alterations revealed by the EEG, such as mirror therapy, functional electrical stimulation and robotics (Jia et al 2022 ; Jaafar et al 2021 ; Daly and Ruff 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the neurophysiological mechanism of mirror therapy is not fully elucidated, recent studies have revealed some possible mechanisms. Mirror therapy can reduce asymmetrical activation between the hemispheres, stimulate the ipsilateral, and the contralateral primary motor cortex, extensively activate the mirror neuron system, and induce partial motor neuron pathways on the affected side, facilitating brain function remodeling ( Deconinck et al, 2015 ; Shih et al, 2017 ; Ding et al, 2019 ; Jaafar et al, 2021 ). Furthermore, the mirror neuron system can contribute to the recovery of limb motor function ( Rizzolatti et al, 2009 ; Garrison et al, 2010 ).…”
Section: Mirror Therapymentioning
confidence: 99%
“…O contexto dessa patologia cerebrovascular provoca um grande problema de saúde pública mundial, no qual apresenta carga global de 59,2%, se tornando um agravo comum na atualidade em questões de morbimortalidade, sequelas, custos médicos e sociais 3 . Ainda, cerca de 90% dos indivíduos sobreviventes permanecem com sequelas funcionais, e somente de 5% a 20% desses atingem uma completa recuperação funcional 4 . Desta forma, o déficit na habilidade motora em pacientes pós-AVC é muito comum.…”
Section: Introductionunclassified